Conundrum and chances of diabetes management in the Western Pacific Region: A narrative review - Yerin Hwang; Hyunmin Lee; Moon‐Kyu Lee (Journal of Diabetes Investigation)
ABSTRACT The prevalence of diabetes is increasing globally, and glucose management is essential for the treatment of diabetes. Most guidelines recommend early intensive therapy and individualized approaches. Although many countries have implemented various guidelines and educational programs to enhance glucose management, the target achievement rate still remains very low. Studies from several countries and regions have identified various factors that influence blood glucose management, either positively or negatively. These factors have been comprehensively incorporated into guidelines to assist people with diabetes and healthcare professionals in following them and/or developing additional guidelines through further research. We and others have suggested that diverse factors should be considered—including comorbidities, age, complications, life expectancy, and pathophysiologic characteristics, such as ethnic differences in insulin sensitivity and secretion. The Western Pacific (WP) region, comprising countries with significant cultural and racial diversity, necessitates customized programs and community‐based management strategies. In this review, we present specific challenges and opportunities for diabetes management identified through a systematic review of the literature from the WP region, along with those common to other regions. To improve healthcare policy and management in the WP region, it is essential to address regional characteristics and the factors that act as either barriers or facilitators to develop strategies for early intensive and individualized therapeutic approaches. Moreover, additional studies on diabetes pathophysiology and management—including pharmacotherapy—are urgently needed.